Racializing Media Policy. - Smith, Jason A. (Emerald points., 2023)
Racializing Media Policycontributes to a wider understanding of the role of policy work in the media systems, examining the ways that race is embedded within those structures. It is an important read for scholars across the Sociology and Media Studies fields, in addition to providing critical context for policymakers.